PERANCANGAN ARENA LATIHAN FUTSAL DI AMUNTAI - Hendy Nanda Wijaya; Nursyarif Agusniansyah (UNIVERSITAS LAMBUNG MANGKURAT, 2026)
The high interest in futsal makes this sport continue to be popular in Amuntai. However, until now there have been no facilities to accommodate futsal training. Therefore, a building in the form of a futsal training arena for young people is needed in order to support this sport to become more popular and develop over time. By using a modern architectural concept that prioritizes the needs of function and simplicity of the building, it is very suitable to be applied to the design of this futsal arena. As a result, the futsal training arena that is designed can meet the needs for more adequate training and competition, and of course also gets support from supporters who can watch training and matches.